Routledge dictionary of language and linguistics - Bussmann, Hadumod; Kazzazi, Kerstin; Trauth, Gregory (London : Routledge, 1996)
A team of over 30 linguists came together for the 'Routledge Dictionary of Language and Linguistics', forming the most comprehensive and up-to-date work of its kind in the English language. In over 2,500 entries, the dictionary provides an exhaustive surrvey of the subdisciplines of linguistics and covers many of the world's languages. With its term-based approach and emphasis on clear analysis, it complements perfectly Routledge's established range of reference material in the field of linguistics. Alphabetically organized, each entry conforms to a structure designed to convey the maximum amount of information and to meet each user's needs. Clear and concise definitions of concepts and themes are complemented by a wealth of extensive cross-references to synonyms and related terms, salient English-language examples and detailed bibliographies. For ease-of-use, the book also contains 38 illustrations indicating and a cumulative bibliography containing hundreds of references.
Includes bibliographical references.
Keywords: Linguistics -- Dictionaries